Publication Trends for Sarcopenia in the World: A 20-Year Bibliometric Analysis - Yuan, Dongliang; Jin, Hongfu; Liu, Qianqi; Zhang, Jinglve; Ma, Boyan; Xiao, Wenfeng; Li, Yusheng (Frontiers in Medicine, 2022)
Background: Sarcopenia, the age-dependent loss of muscle mass and function, is a common condition among older adults. There has been tremendous change on sarcopenia research in the past 20 years in the world. This study aimed to analyze global trends in this filed. Methods: Using terms “sarcopenia”, we retrieved related publications from the Web of Science (WOS) database and PubMed database. From different aspects, such as the number of papers, total citations, average citations per item, h-index, research area, article types, institutions, country, journals and funding, global sarcopenia publications were classified and analyzed. The software VOS viewer was used for co-occurrence, bibliographic coupling, co-citation, co-authorship analysis and to investigate the publication trends in sarcopenia. Results: From 2001 to 2020, 13421 articles regarding sarcopenia research were published worldwide. The USA made the highest contributions to the global research with the most citations and the highest H-index. Geriatrics gerontology was the main research categories and basic research dominated sarcopenia’s publications, accounting for 16.496% of global publications. Osteoporosis International is the most contribution journal in the world with the largest number of publications. UNITED STATES DEPARTMENT OF HEALTH HUMAN SERVICES was the main funding organization, which sponsored 1604 articles, ranking first. Conclusion: Global sarcopenia research increased rapidly from the 2001 to 2020, especially in recent years. The USA was still the leader of sarcopenia research. In the future, the study of sarcopenia will continue to focus on aging, nutrition and exercise, and will delve deeper into molecular mechanisms. On the other hand, revealing the link between sarcopenia and other diseases will be the next research hotspot.